Association between peri-implantitis and systemic inflammation: a systematic review - Yan, Yumeng; Orlandi, Marco; Suvan, Jeanie; Harden, Simon; Smith, Jacqueline; D’Aiuto, Francesco (Frontiers in Immunology, 2023)
Background: Peri-implantitis is an infectious/inflammatory disease with similar clinical and radiographic features to periodontitis. Overwhelming evidence confirmed that periodontitis causes elevations in systemic inflammatory mediators, this is unclear for peri-implantitis hence this study aimed to appraise all available evidence linking peri-implantitis with systemic inflammation.: A systematic review was completed according to PRISMA guidelines. Eight electronic databases (Cochrane Central Register for Controlled Trials, MEDLINE, EMBASE, Web of Science, Dentistry & Oral Sciences Source, Scopus, LILACS and China Online), ClinicalTrials.gov, WHOICTRP and grey literatures were searched up to 9 th , February 2023. Human studies of randomized controlled trials, nonrandomized intervention studies, cohort studies, case control, and crosssectional studies were eligible for inclusion. Quantitative analyses were performed using random effects models.Results: A total of 27 full text articles were retrieved and 11 clinical studies were included in the final analyses. All evidence gathered demonstrated a consistent association between peri-implantitis and systemic inflammation. Patients with peri-implantitis exhibited higher levels of serum C-Reactive Protein (CRP) (SMD: 4.68, 98.7% CI: 2.12 to 7.25), interleukin-6(IL-6) (WMD: 6.27 pg/ml, 0% CI: 5.01 to 7.54) and of white cell counts (WMD: 1.16 *10 3 /μL, 0% CI: 0.61 to 1.70) when compared to participants without peri-implantitis.Peri-implantitis is associated with higher systemic inflammation as assessed by serum CRP, IL-6 and white cell counts. Further research is needed to clarify the nature of this association.